Kinetic-Spectrophotometric Determination of Tungsten(VI) Based on Azure I-Ti(III) Reaction in the Presence of Thiocyanate as an Activator - POURREZA*, N.; NIROOMAND, S. (Asian Journal of Chemistry, 2010)
The catalytic effect of tungsten(VI) and activating effectof thiocyanate on the reduction reaction of Azure I by Ti(III)was used to develop a sensitive and rapid kinetic spectrophotometricmethod for the determination of tungsten(VI). Thereaction was monitored spectrophotometrically by measuringthe change in absorbance (ΔA) at 646 nm using a fixedtime method (2.5 min). The effect of different variables onthe reaction was investigated and optimized in order to achievethe highest sensitivity. The calibration graph was linearin the range 5-90 ng mL-1 and the detection limit was 2.9ng mL-1. The relative standard deviation for ten replicatemeasurements of 10 and 50 ng mL-1 of tungsten was 4.7 and3.5, respectively. The method was successfully applied to thedetermination of tungsten in spring water samples.